Assessment of hydroalcoholic and hexane extracts of Rosa persica Mich. flower on rat ileum spasm - Hassan Sadraei; Gholamreza Asghari; Fatemeh Jalali (Wolters Kluwer Medknow Publications, 2016)
It has been reported that Rosa damascena hydroalcoholic extract has inhibitory effect at higher concentration but stimulatory action at lower concentrations on ileum. This could be due to the presence of stimulatory components in the extract. R. persica Mich. is another species which belongs to Rose family but so far there is no report about pharmacological action of its extract. Therefore, the objective of this research was to investigate inhibitory effect of hydroalcoholic and hexane extract of this plant on ileum contraction to see which type of extract would be more appropriate as antispasmodic agents. Hydroalcoholic and hexane extracts were prepared by percolation method. A section of rat ileum was suspended in an organ bath containing Tyrode's solution. The tissue was kept under 1 g tension at 37 °C and continuously gassed with O 2 . Effects of R. persica extracts or vehicle were studied on ileum contractions induced by electrical field stimulation (EFS), KCl or acetylcholine (ACh) and compared with that of atropine. Hydroalcoholic extracts of R. persica (10-640 μg/ml) concentration dependently inhibited ileum contraction induced by KCl (IC 50 = 244 ± 35 μg/ml), ACh (IC 50 = 129 ± 7.4 μg/ml) and EFS (IC 50 = 172 ± 18.7 μg/ml). Hexane extract of R. persica (10-320 μg/ml) concentration dependently inhibited ileum contraction induced by KCl (IC 50 = 117 ± 12.4 μg/ml), ACh (IC 50 = 78 ± 9.1 μg/ml) and EFS (IC 50 = 67 ± 10.5 μg/ml). Atropine only inhibited the responses to ACh and EFS. The vehicle had no significant effect on ileum contractions. From this experiment it was concluded that R. persica extract have inhibitory effect on rat isolated ileum. Therefore, separation and identification of active component is recommended.